The effect of promotion on sales at PT. 3M Indonesia Surabaya Branch - Akhmad Nasir; Damarsari Ratnasahara Elisabeth; Joko Suyono; Rurit Irma Ifadah (IJEBD International Journal Of Entrepreneurship And Business Development eISSN 2597-4785 pISSN 2597-4750)
The purpose of this study is to determine the effect of promotion on sales at PT. 3M Indonesia Surabaya Branch. The sample used in this study amounted to 30 consumers. The analysis technique used is simple linear regression analysis and simple determination. In order to test the effect of partial and simultaneous of these independent variables, the researcher conducted a partial test (t test) and simultaneous test (F test). The variables used are sales (Y) and promotion (X) and data analysis tool using simple regression formula, correlation coefficient and determination. The results of the study show that the regression equation is Y = 17,020 + 0,320 (x) with Y value of 17,020 which means that if the promotion (X) value is 0, then sales (Y) is 17,020. And the promotion variable regression coefficient (X) is 0.320. This means that if promotion (X) increases by 1 unit, then an increase in sales (Y) will increase by 0.320. Based on the results of the correlation coefficient test shows a positive value, meaning that Ho is rejected and Ha is accepted, it can be concluded that there is a significant effect between promotion and sales at PT. 3 M Indonesia Surabaya Branch.